(untitled) (CIPEEX, 2026)
Ibuprofen (IBU) is a widely used nonsteroidal anti-inflammatory drug, but it has significant pharmacokinetic limitations, such as low aqueous solubility, moderate lipophilicity, and polymorphic instability, which compromise its bioavailability and clinical efficacy. This work proposes a multidisciplinary analysis of IBU, ranging from structural characterization by crystallography and molecular modeling to the development and evaluation of nanoemulsified (IBN) and emulsified (IBE) formulations. The crystal structure was investigated by X-ray diffraction, identifying polymorphic form I (space group P2₁/c), considered more thermodynamically stable (Dudognon et al., 2008). Hirshfeld surface and molecular fingerprints revealed significant intermolecular interactions, contributing to the understanding of the molecule’s stability. In vivo assays were performed to compare the antinociceptive and anti-inflammatory properties of the formulations. IBN exhibited smaller particle size, reduced polydispersity index, and greater colloidal stability, resulting in superior therapeutic efficacy and reduced potential toxicity. Computational analysis indicated that the electronic structure of IBU favors its formulation in nanometric systems, due to its low polarity and moderate lipophilicity. The results demonstrate that nanoemulsion constitutes an effective strategy for overcoming the limitations of conventional formulations, increasing drug solubility, bioavailability, and stability. This study reinforces the importance of integrating structural approaches and nanotechnology in the rational development of advanced drug delivery systems.